2006
DOI: 10.1016/j.febslet.2006.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Extensive adenosine‐to‐inosine editing detected in Alu repeats of antisense RNAs reveals scarcity of sense–antisense duplex formation

Abstract: One type of RNA editing converts adenosine residues to inosine in double-stranded regions. Recent transcriptome analysis has revealed that numerous Alu repeats, present within introns and untranslated regions of human transcripts, are subject to this A fi I RNA editing. Furthermore, it revealed global transcription of antisense RNAs. Here, we demonstrate that antisense RNAs are also edited extensively but only in their Alu repeat sequences, and editing does not extend to the surrounding sequence. Our findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 24 publications
3
39
0
Order By: Relevance
“…However, A→I RNA editing is not detected in the regions outside of repetitive sequences 75 . PCR after reverse transcription of RNA (RT-PCR) and sequencing analysis of sense and antisense cyclin CNNM3 RNAs derived from an intronic region that contains two inverted Alu repeats confirmed that both sense and antisense RNAs are extensively edited, but only in their intramolecular fold-back dsRNA structures 76 (FIG. 4b).…”
Section: Editing Of Non-coding Antisense Transcriptsmentioning
confidence: 94%
See 4 more Smart Citations
“…However, A→I RNA editing is not detected in the regions outside of repetitive sequences 75 . PCR after reverse transcription of RNA (RT-PCR) and sequencing analysis of sense and antisense cyclin CNNM3 RNAs derived from an intronic region that contains two inverted Alu repeats confirmed that both sense and antisense RNAs are extensively edited, but only in their intramolecular fold-back dsRNA structures 76 (FIG. 4b).…”
Section: Editing Of Non-coding Antisense Transcriptsmentioning
confidence: 94%
“…4b). No editing was detected outside of the Alu sequences, which indicates that the formation of an intermolecular sense-antisense RNA duplex does not occur 76 (FIG. 4c).…”
Section: Editing Of Non-coding Antisense Transcriptsmentioning
confidence: 96%
See 3 more Smart Citations